An Efficient Method for the Reduction of Cephalosporin Sulfoxide - SINGH, DAROGA; SINGH, VANDANA; PRAKASH RAI, BISHWA (Asian Journal of Chemistry, 2010)
An efficient method for the reduction of cephalosporin sulfoxide to their corresponding sulfide using TiCl4/NaI reagent system.